A systematic analysis of mutual effects of transportation noise and air pollution exposure on myocardial infarction mortality: a nationwide cohort study in Switzerland. (24th October 2018) - Héritier, Harris; Vienneau, Danielle; Foraster, Maria; Eze, Ikenna C; Schaffner, Emmanuel; de Hoogh, Kees; Thiesse, Laurie; Rudzik, Franziska; Habermacher, Manuel; Köpfli, Micha; Pieren, Reto; Brink, Mark; et al.
Abstract: Aims: The present study aimed to disentangle the risk of the three major transportation noise sources—road, railway, and aircraft traffic—and the air pollutants NO2 and PM2.5 on myocardial infarction (MI) mortality in Switzerland based on high quality/fine resolution exposure modelling. Methods and results: We modelled long-term exposure to outdoor road traffic, railway, and aircraft noise levels, as well as NO2 and PM2.5 concentration for each address of the 4.40 million adults (>30 years) in the Swiss National Cohort (SNC). We investigated the association between transportation noise/air pollution exposure and death due to MI during the follow-up period 2000–08, by adjusting noise [Lden (Road), Lden (Railway), and Lden (Air)] estimates for NO2 and/or PM2.5 and vice versa by multipollutant Cox regression models considering potential confounders. Adjusting noise risk estimates of MI for NO2 and/or PM2.5 did not change the hazard ratios (HRs) per 10 dB increase in road traffic (without air pollution: 1.032, 95% CI: 1.014–1.051, adjusted for NO2 and PM2.5 : 1.034, 95% CI: 1.014–1.055), railway traffic (1.020, 95% CI: 1.007–1.033 vs. 1.020, 95% CI: 1.007–1.033), and aircraft traffic noise (1.025, 95% CI: 1.006–1.045 vs. 1.025, 95% CI: 1.005–1.046). Conversely, noise adjusted HRs for air pollutants were lower than corresponding estimates without noise adjustment. Hazard ratio per 10 μg/m³ increase with and without noise adjustment were 1.024 (1.005–1.043) vs. 0.990 (0.965–1.016) for NO2 and 1.054 (1.013–1.093) vs. 1.019 (0.971–1.071) for PM2.5 . Conclusion: Our study suggests that transportation noise is associated with MI mortality, independent from air pollution. Air pollution studies not adequately adjusting for transportation noise exposure may overestimate the cardiovascular disease burden of air pollution.